Holocene intracontinental deformation of the northern North China Plain: Evidence of tectonic ground fissures. (1st April 2016) - Xu, Liqing; Li, Sanzhong; Cao, Xianzhi; Somerville, I.D.; Suo, Yanhui; Liu, Xin; Dai, Liming; Zhao, Shujuan; Guo, Lingli; Wang, Pengcheng; Cao, Huahua
Highlights: The Longyao Ground Fissures are a result of creeping of WNW-trending fault. Two sets of tectonic ground fissures are well developed in the northern North China Plain. Holocene deformation is characterized by NNW-tilting and partial conjugate faulting. Abstract: Following the collecting and analyzing of field data on the geometry and kinematics characteristics of ground fissures in the northern North China Plain (NNCP), this paper shows that en échelon ground fissures or tectonic ground fissures with a length of several meters to tens of kilometers extending along active faults are possibly controlled by underlying active faults. There are two groups of tectonic ground fissures developed in the NNCP. One group consists of ENE-trending "right-stepping" ground fissures, some of which have a component of sinistral motion. The other group is NNE-trending "left-stepping" ground fissures with dextral motion. A large amount of data from trenches, boreholes and seismic exploration reflect that they are active-faulting-related. The NNW-trending regional extensional stress field and the reactivation of pre-existing faults are the major factors controlling ground fissures. Data from the Quaternary sedimentary records, deep incised valleys, the distribution of earthquakes and ground fissures, and our field work show that the Holocene intracontinental deformation of the NNCP is characterized by intense faulting and northwestward tilting, which may be related to a NNW–SSE-oriented tensional stress field in the shallow crust and asthenospheric upwelling in the mantle.